Perception of oral health in older adults in Corrientes, Argentina - Dho, María Silvina (2022)
Objective. Describe the perception of oral health in older adults who attend Grandparents’ Clubs and a university dental clinic. Methods. Descriptive, cross-sectional study was conducted in the city of Corrientes, Argentina, in 97 adults over 60 years old. An interrogation and oral clinical examination were performed. To assess the perception of oral health, the Assessment Index in Oral Health in Geriatrics (GOHAI) was used. Results. The 97 older adults who participated, 75.3% (n=73) corresponded to the female sex. The mean age of the population was 67.1 ± 4.4 years, it was observed that for 86.4% the self-perception of their oral health is negative. When comparing the group of older adults who attend Grandparents’ Clubs and the older adults who attend the dental clinic, statistically significant differences were found in the perception of oral health (p = 0.0001). No statistically significant association was found with age (p=0.28), sex (p=0.50), marital status (p=0.45), educational level (p=0.06), occupation (p=0.68), suffering from systemic diseases (p=0.52) and DMFT caries index (p=0.09). Conclusions. In the Older Adults who participated in the study, the negative perception of their oral health predominates, especially in those who sought dental care.